Producto comunicacional :Revista Memoria Social de la Parroquia de Amaguaña. - Gualotuña, Carlos Gustavo (2014)
The project communicative product "Love Huañuy" is defined as a magazine publisher, whose support is the Andean identity of the inhabitants of the parish of Amaguaña. His communicative essence lies in the collection and dissemination of social memory of said place, in order that their culture prevail. The magazine "Love Huañuy" after a thorough investigation and evaluation of the data, offers historical and cultural themes of the parish of Amaguaña since its purpose is to become a tool of opinion and discussion within the amagüañense cultural context.